The Argus-II Retinal Prosthesis Implantation; From the Global to Local Successful Experience - Farvardin, Mohsen; Afarid, Mehrdad; Attarzadeh, Adel; Johari, Mohammad K.; Mehryar, Morsal; Nowroozzadeh, M. Hossein; Rahat, Feisal; Peyvandi, Hossein; Farvardin, Reza; Nami, Mohammad (Frontiers in Neuroscience, 2018)
Over the past few years, visual prostheses (namely, Argus II retinal implant) and gene therapy have obtained FDA approval in treating blindness resulting from retinitis pigmentosa. Compared to gene therapy; Argus II is less costly with a demonstrated favorable outcome, though the vision is yet artificial. To obtain better results, expectation counseling and preoperative retinal assessment are critical. The global experience with Argus II has enrolled no more than 300 cases so far. The first Argus II retinal prosthesis in Iran was successfully implanted in Shiraz (October 2017). To date, Argus II artificial retina is implanted in four patients in Iran. Beside successful surgery and post-operative care, rehabilitation efforts with validated outcome measures including visual rehabilitation together with neurovisual, visuo-constructive and cognitive rehabilitation/empowerment approaches are expected to boost the functional outcome. A multidisciplinary approach within a cross-functional team would optimize strategies towards better patient outcomes. As such, establishing a collaborative network will foster organized research efforts to better define outcome assessment and rehabilitation strategies. This opinion paper has been an attempt to provide an overview of Argus-II retinal implant global experience as well as the clinical outcome of the so far cases in Iran. Insights from this review were communicated during the first “Brain Engineering and Computational Neuroscience Conference”, 31 January-2 February 2018 in Tehran.